Adult liver transplant anesthesiology practice patterns and resource utilization in the United States: Survey results from the society for the advancement of transplant anesthesia. Issue 1 (26th October 2021) - Crouch, Cara; Sakai, Tetsuro; Aniskevich, Stephen; Damian, Daniela; De Marchi, Lorenzo; Kaufman, Michael; Kumar, Sathish; Little, Michael; McCluskey, Stuart; Pivalizza, Evan; Sellers, Daniel; Sridhar, Srikanth; et al.
Abstract: Introduction: Liver transplant anesthesiology is an evolving and expanding subspecialty, and programs have, in the past, exhibited significant variations of practice at transplant centers across the United States. In order to explore current practice patterns, the Quality & Standards Committee from the Society for the Advancement of Transplant Anesthesia (SATA) undertook a survey of liver transplant anesthesiology program directors. Methods: Program directors were invited to participate in an online questionnaire. A total of 110 program directors were identified from the 2018 Scientific Registry of Transplant Recipients (SRTR) database. Replies were received from 65 programs (response rate of 59%). Results: Our results indicate an increase in transplant anesthesia fellowship training and advanced training in transesophageal echocardiography (TEE). We also find that the use of intraoperative TEE and viscoelastic testing is more common. However, there has been a reduction in the use of veno‐venous bypass, routine placement of pulmonary artery catheters and the intraoperative use of anti‐fibrinolytics when compared to prior surveys. Conclusion: The results show considerable heterogeneity in practice patterns across the country that continues to evolve. However, there appears to be a movement towards the adoption of specific structural and clinical practices.